Effect of dietary fats and metabolic determinants on chylomicron metabolism - Irawati, Deasy (Curtin University, 2016)
Atherosclerosis is initiated by the retention of remnant lipoproteins in the arterial subendothelial space. Indeed results from animal and human studies have demonstrated the presence of chylomicron remnants in atherosclerotic lesions. The dietary fatty acid composition has been recognised to modulate postprandial chylomicron response. This thesis explores the interactive effects of dietary fatty acid composition and physiological determinants on postprandial chylomicron response, specifically the pro-atherogenic remnant lipoprotein fraction.